Understanding the effects of agricultural R&D investments on poverty and undernourishment in sub-Saharan Africa: A causal mediation approach - Benfica, Rui; Nin-Pratt, Alejandro (International Food Policy Research Institute, 2021)
This analysis explores the relationship between agricultural R&D investments and rural poverty reduction, and the prevalence of undernourishment in sub-Saharan Africa (SSA). It uses a panel data set of internationally comparable poverty dis-aggregated by urban and rural areas, country level undernourishment, and ASTI data on R&D investments and derived indicators. The study uses agricultural R&D knowledge stocks (KS) to account for the lagged effects of research through depreciation and gestation period of investments, and applies causal mediation analysis to assess the impact of KS on poverty and hunger and measure the relative contribution of KS-induced agricultural productivity growth on those outcomes. Evidence suggests that, while SSA growth in KS has been relatively slow, it helped reduce rural poverty and undernourishment – the percentage point reduction in rural extreme and moderate poverty of a 1% annual increase in KS is 0.218 and 0.146 percentage points per year, respectively. Mediation analysis indicates that a fifth of the KS effect on extreme rural poverty, and a quarter of the KS effect on moderate rural poverty, can be attributed to KS driven gains in agricultural labor productivity. Likewise, KS growth reduces undernourishment – a 1% annual increase in KS leads to a drop of 0.132 percentage points per year in the prevalence of undernourishment, with about 40% of that effect mediated through gains in agricultural land productivity. These results indicate that KS supports poverty and hunger reduction through benefits on-farm and beyond it. They also suggest that there is room for strengthening the role of R&D KS productivity enhancing innovations. Given the current low levels of investments in R&D and resulting KS, increasing its levels will be critical, but that alone is not sufficient. makers will have to rethink the way the innovations from R&D get scaled up and pay attention to the necessary complementary policies and investments that enable a sustainable pathway leading to greater productivity growth and development impacts.